Quranic Studies: Ber-Ushul Fiqh dengan Maqashid Syariah Sebagai Metode dalam Perspektif Yudian Wahyudi - Sadari, S (IAIN Surakarta, 2018)
This article offers the maqasyid as method rather than doctrine, method is a process of developmental dynamics, whereas doctrine is a stalled idea of development. The findings are productivity of thinking that can be accounted scientifically both quantity and quality. Its usul fiqh literary ground